Citral como aditivo na ração para peixes marinhos com diferentes hábitos alimentares: enzimas digestivas e parâmetros zootécnicos e metabólicos - Michelotti, Bruna Tomazetti (2020)
Essential oils whose major compound is citral have been showing good results when used as additives in fish feed. This work tested dietary citral supplementation for three species with three distinct feeding habits, namely: common snook (Centropomus undecimalis; carnivore); mullet (Mugil liza; detritivore) and Brazilian sardine (Sardinella brasiliensis; omnivore). The levels used were: 0.0 - control, 0.5, 1.0 and 2.0 mL of citral per kg of feed. The citral used in the different diets was a commercial mixture containing α- citral = 60.15% and β- citral = 39.85%. The first two experiments (common snook and mullet) had a 45-day feeding period and did not show any mortality, however very different results. The citral at the lowest dietary insertion level was harmful to common snook, and at the end of the experimental period, the treatment with 0.5 mL of citral per kg of feed showed the lowest weight gain and specific growth rate and the highest feed conversion. Pepsin activity was higher in the stomach of fish fed 0.5 mL of citral per kg of feed and amylase activity was greater in the intestine of fish fed mL of citral per kg of feed compared to the control group. Intestinal lipase activity was higher in all groups fed with citral compared to the control group. Chymotrypsin and trypsin activities showed no difference between groups. The highest dietary citral level (2.0 mL of citral per kg of diet) for the mullet caused higher weight gain than the control treatment. Fish fed with 2.0 mL of citral / kg of feed showed greater pepsin activity in the stomach and amylase in the intestine than the control fish. However, dietary citral does not have a dose-response relationship with any of the tested parameters. The experiment conducted with the Brazilian sardine in a stressful situation due to the sudden changes in luminosity showed mortality in all treatments and lasted for 20 days. Survival was greater in treatments containing citral. Despite improving the activity of some digestive enzymes, no beneficial effect of supplementation with citral was observed in the growth of this species. It is concluded that citral acts differently in the species tested and we recommend its use as an additive in the diet for mullet and sardine.